Strategi Pengembangan Bidang Akademik di Pondok Pesantren Darul Hikmah Tulungagung - Pendik Hanafi (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2024)
Understanding the realization of a science institution that is able to produce graduates who are noble, competitive, and able to raise the level of Islamic science so that it can compete with other science institutions. by trying to concentrate on improving institutional administration with an emphasis on developing academic fields. Qualitative research methodology is applied. Documentation, observation, and interviews are used as data collection methods. Data collection techniques include documentation, observation, and interviews. Data reduction, data presentation (data display), and drawing conclusions/verification are three data analysis procedures used. The academic development plan of the Darul Hikmah Islamic Boarding School in Tulungagung is based on the following findings: 1) conditions that encourage institutional progress; a) effective leadership through the development of institutional vision and its implementation in the classroom b) increasing learning resources; c) providing additional staff assistance to qualified teachers. 2) Opinions about science A) the ability to distinguish between good and bad in relation to institutional development; B) the ability to work with people in any form; and C) the existence of distinctive characteristics in the organization. 3) Comply with regulations, the Ministry of National Science Planting, and the community Building a positive culture; 5) Improve the experience of Science Planting.